Surface photovoltage properties and photocatalytic activities of nanocrystalline CoFe2O4 particles with porous superstructure fabricated by a modified chemical coprecipitation method - Zhu, Z.; Li, Xin Yong; Zhao, Q.; Shi, Y.; Li, H.; Chen, G. (2011)
In this study, nanocrystalline CoFe2O4 particles with porous timber-like superstructure were synthesized by a modified chemical co-precipitation route with calcination temperatures of 573, 673, 773, 873, and 973 K, respectively. The structural properties of the samples were systematically investigated by X-ray powder diffraction, scanning electronic microscopy, energy-dispersive X-ray spectra, UV-Vis diffuse reflectance spectroscopy, and Fourier transform infrared spectroscopy techniques. The photo-induced charge separation in the samples was demonstrated by surface photovoltage (SPV) measurement. The photocatalytic performances of the CoFe 2O4 samples were comparatively studied by the degradation of 4-chlorophenol under Xe lamp irradiation. The results indicated that the sample calcined at 673 K exhibited the highest photocatalytic efficiency among the five samples. © Springer Science+Business Media B.V. 2010.